Effort–reward imbalance at work, over-commitment personality and diet quality in Central and Eastern European populations. Issue 7 (12th February 2016) - Chen, Sung-Wei; Peasey, Anne; Stefler, Denes; Malyutina, Sofia; Pajak, Andrzej; Kubinova, Ruzena; Chan, Jen-Hui; Bobak, Martin; Pikhart, Hynek
Abstract: The aims of this study were to investigate the associations between work stress defined by the effort–reward imbalance (ERI) model and diet quality and to examine the potential role of over-commitment (OC) personality in ERI–diet relationships. A cross-sectional study was conducted in random population samples of 6340 men and 5792 women (age 45–69 years) from the Czech Republic, Russia and Poland. Dietary data were collected using FFQ. The healthy diet indicator (HDI) was constructed using eight nutrient/food intakes (HDI components) to reflect the adherence to WHO dietary guideline. The extent of imbalance between effort and reward was measured by the effort:reward (ER) ratio; the effort score was the numerator and the reward score was multiplied by a factor adjusting for unequal number of items in the denominator. Logistic regression and linear regression were used to assess the associations between exposures (ER ratio and OC) and outcomes (HDI components and HDI) after adjustment for confounders and mediators. The results showed that high ER ratio and high OC were significantly associated with unhealthy diet quality. For a 1-sd increase in the ER ratio, HDI was reduced by 0·030 and 0·033sd in men and women, and for a 1-sd increase in OC, HDI was decreased by 0·036 and 0·032sd in men and women, respectively. The modifying role of OC in ERI–diet relationships was non-significant. To improve diet quality at workplace, a multiple-level approach combining organisational intervention for work stress and individual intervention for vulnerable personality is recommended.